Initial experiences of inventories of greenhouse gas emissions at the local level in Costa Rica - García Sánchez, Daniela (2021)
[Introduction]: In Costa Rica the main source of greenhouse gas (GHG) emissions at the national scope is the energy sector, mainly transport. These emissions are expected to result from activities taking place in urban areas. [Objective]: Determine the main sectors and sources of GHG emissions at the local level and identify lessons and opportunities to promote strategies aimed at decarbonized development. [Methodology]: The methodology applied was the one used in the Cantonal Category of the Carbon Neutral Country Program 2.0 (PPCNC) for the transport, energy, waste, agriculture, and the voluntary industry sectors and the use of products in five cantons (Belén, Desamparados, Golfito, La Unión, and San José) and two districts (Monte Verde and Puntarenas). [Results]: Higher emissions were reported by urban cantons while lower ones were in small rural and coastal districts. The transport sector is the main source of emissions, except for Belén where it was surpassed by the energy sector for industrial use. Data per capita shows that small districts can have higher levels of emissions per person than urban cantons. [Conclusions]: At the local scope, the main sources of emissions can vary, depending on the socioeconomic and demographic characteristics of the canton or district. The inventory provides information to make local decisions, prioritize mitigation actions complying with national decarbonization targets, and monitor the impact of climate action, both locally and nationally.